EFFECTIVENESS OF GROUP COUNSELING BASED ON ALTHOUGH APPROACH ON ELDERLY DEPRESSION - FATEMEH SALEHI (Studia Universitatis Babes-Bolyai, 2013)
ABSTRACT. Seniors are an asset to society and investment in their health that will benefit each community. This study examined the effectiveness of group counseling based on although approach on reduction of depression in elderly. The population consisted of all elderly residents of nursing homes in the city of Amol, of which twenty were selected according to depression scores. Those who had higher scores were randomly divided into two control and experimental groups (ten in each group). The method of testing was pretest-posttest with control group. A depression test instruments used in this research to measure elderly depression of both group before and after the tests, the subjects in both groups responded to it. An organized set of activities executed based on experimental techniques, although the intervention was implemental. Using analysis of covariance and t-test, the main findings of this study indicated that the group consulting has significant impact on improving depression. This approach is based on the use of group counseling for elderly depression treatment as an appropriate model for seniors offered counseling.